2015
DOI: 10.1039/c5tc01584g
|View full text |Cite
|
Sign up to set email alerts
|

Band gap control and transformation of monolayer-MoS2-based hetero-bilayers

Abstract: Study of heterostructured bilayer systems is an essential prerequisite for developing twodimensional nano-electronic devices. Using ab initio density functional theory calculations, we investigated the atomic and electronic properties of hetero-bilayers composed of silicene and germanene layers with monolayer MoS2. Our results show that both Silicene-MoS2 and Germanene-MoS2 hetero-bilayers are direct band gap semiconductors. The band gaps of silicene and germanene in hetero-bilayers are opened due to the subla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
(163 reference statements)
2
15
0
Order By: Relevance
“…The lattice constants of SiS 2 and WSe 2 monolayers are calculated to be 3.30 and 3.33 Å, respectively, which agree well with previous results [ 33 , 41 , 42 ]. Compared with the hybrid systems investigated previously [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], such a lattice mismatch (only about 0.9%) between the SiS 2 and WSe 2 monolayers is very small. Thus, we have employed supercells composed of 1 × 1 unit cells of SiS 2 monolayer and 1 × 1 unit cells of WSe 2 monolayer in the x-y plane.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The lattice constants of SiS 2 and WSe 2 monolayers are calculated to be 3.30 and 3.33 Å, respectively, which agree well with previous results [ 33 , 41 , 42 ]. Compared with the hybrid systems investigated previously [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], such a lattice mismatch (only about 0.9%) between the SiS 2 and WSe 2 monolayers is very small. Thus, we have employed supercells composed of 1 × 1 unit cells of SiS 2 monolayer and 1 × 1 unit cells of WSe 2 monolayer in the x-y plane.…”
Section: Resultsmentioning
confidence: 67%
“…Aretouli et al found that SnSe 2 /WSe 2 heterostructure possesses a broken gap configuration, indicating that band-to-band tunneling through an ultrathin van der Waals gap can be switched on and off easily via applying a small bias across the interface, which implies promising applications in 2D-2D vertical TFETs [ 29 ]. Thus, the heterostructures not only provide a new way to enrich the novel properties of the system but also to well preserve the electronic properties of the original freestanding two single-layer 2D components [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, two-dimensional (2D) transition metal dichalcogenide (TMDC) materials with the generalized formula MX 2 (M = Mo, W; X = S, Se, and Te) have received burgeoning research interest due to their peculiar physicochemical properties. [1][2][3][4][5] Their electronic states generally are subject to strong interlayer coupling and undergo transitions from the indirect bandgap in the bulk form to the direct bandgap in monolayers. In particular, the direct bandgap energy in many monolayer TMDCs lies in the visible and near infrared range, making them ideal candidates for 2D optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, molybdenum disulde (MoS 2 ) as an p-type semiconductor with a band gap energy approximately 1.9 eV (ref. 25 ) has been investigated as a suitable material owing to its unique properties like low toxicity, high catalytic performance, thermal and chemical stability, and high absorption capacity. In this regard, MoS 2 has been widely applied in multiple applications such as super capacitors, sensors, Li-ion batteries, photocatalysts and more.…”
Section: Introductionmentioning
confidence: 99%